2020
DOI: 10.3390/biom10060962
|View full text |Cite
|
Sign up to set email alerts
|

Prolyl Endopeptidase-Like Facilitates the α-Synuclein Aggregation Seeding, and This Effect Is Reverted by Serine Peptidase Inhibitor PMSF

Abstract: The aggregation of α-synuclein (α-Syn) is a characteristic of Parkinson’s disease (PD). α-Syn oligomerization/aggregation is accelerated by the serine peptidase, prolyl oligopeptidase (POP). Factors that affect POP conformation, including most of its inhibitors and an impairing mutation in its active site, influence the acceleration of α-Syn aggregation resulting from the interaction of these proteins. It is noteworthy, however, that α-Syn is not cleaved by POP. Prolyl endopeptidase-like (PREPL) protein is str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Recently, Santos et al. also revealed that PREPL facilitates α-synuclein aggregation through a non-hydrolytic mechanism similar to that observed for PREP ( Santos et al., 2020 ). The relatively low activity of PREPL toward the ester substrates in vitro fits such a model.…”
Section: Discussionmentioning
confidence: 54%
“…Recently, Santos et al. also revealed that PREPL facilitates α-synuclein aggregation through a non-hydrolytic mechanism similar to that observed for PREP ( Santos et al., 2020 ). The relatively low activity of PREPL toward the ester substrates in vitro fits such a model.…”
Section: Discussionmentioning
confidence: 54%
“…Recent findings suggest that protein-protein interactions are pivotal for the function of PREPL and that some of these interactions are independent of catalytic activity (15,19,20). Therefore, we evaluated if the CMS22 patient mutations have an effect on the interactome of PREPL.…”
Section: ) Patient Mutations In Prepl Disrupt Protein-protein Interac...mentioning
confidence: 99%
“…This phenotype was rescued with a catalytically inactive PREPL p.Ser559Ala variant, suggesting a catalytic independent mechanism. Moreover, PREPL interacts with α-synuclein, thereby influencing aggregation, without α-synuclein cleavage (20). For PREP, a homologue of PREPL, substrate binding in the catalytic site is thought to result in an allosteric change that alters protein-protein interactions (21).…”
Section: Introductionmentioning
confidence: 99%
“…The biological functions described in the section below include microbial invasion through the protective barrier, pathophysiology of human diseases, and plant nutrient uptake/mobilization, growth, and development. Apart from proteolysis, PPCEs can affect the biological system through protein–protein interactions (PPIs), such as the acceleration of α-synuclein aggregation that can lead to Parkinson’s disease [ 8 ]. Hence, studies of PPCEs are important for the pharmaceutical industries.…”
Section: Introductionmentioning
confidence: 99%